Pengaruh Brand Equity Terhadap Keputusan Pembelian Produk Pisang Cavendish Merek Sunpride di Pasar Swalayan Kota Jakarta Selatan - Arda Govar Parsaoran Rajagukguk; Endang Siti Rahayu; Heru Irianto (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2024)
Bananas are the most widely consumed fruit. Sunpride cavendish bananas are a primary choice for consumers when purchasing bananas. This study examines the influence of brand equity elements, including brand awareness, perceived quality, brand associations, and brand loyalty, on the purchasing decisions of Sunpride Cavendish bananas in supermarkets in South Jakarta. This research employs a descriptive quantitative approach. The research location was determined using purposive sampling because South Jakarta residents have a consumptive and modern lifestyle, and their consumption expenditures are among the highest. The sample in this study consisted of 100 respondents. The research instrument used was a questionnaire. The results show that brand equity elements collectively influence the purchasing decisions of Sunpride cavendish bananas in South Jakarta. Brand associations were found to be the most dominant element influencing the purchasing decisions of Sunpride cavendish bananas in supermarkets in South Jakarta.